2013
DOI: 10.1093/jxb/ert386
|View full text |Cite
|
Sign up to set email alerts
|

In vivomonoubiquitination of anaplerotic phosphoenolpyruvate carboxylase occurs at Lys624 in germinating sorghum seeds

Abstract: Phosphoenolpyruvate carboxylase (PEPC; EC 4.1.1.31) is an important cytosolic regulatory enzyme that plays a pivotal role in numerous physiological processes in plants, including seed development and germination. Previous studies demonstrated the occurrence of immunoreactive PEPC polypeptides of ~110kDa and 107kDa (p110 and p107, respectively) on immunoblots of clarified extracts of germinating sorghum (Sorghum bicolor) seeds. In order to establish the biochemical basis for this observation, a 460kDa PEPC hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…In castor bean, comparable p107 and p110 PEPC proteins were shown by peptide mass spectrometry to be derived from the same RcPEPC gene (Uhrig et al ., ). Likewise, the p107 and p110 proteins in harsh hakea ( Hakea prostrata ) and sorghum ( Sorghum bicolor ) were confirmed to have single‐gene origin from the corresponding HpPEPC and SbPEPC genes (Shane et al ., ; Ruiz‐Ballesta et al ., ), suggesting that a similar relationship may exist for the p107 and p110 PEPC proteins in A. thaliana . The percentage of p110 was approximately 40% lower in the induced TPS29.2 plants than in the controls (Figure a).…”
Section: Resultsmentioning
confidence: 86%
“…In castor bean, comparable p107 and p110 PEPC proteins were shown by peptide mass spectrometry to be derived from the same RcPEPC gene (Uhrig et al ., ). Likewise, the p107 and p110 proteins in harsh hakea ( Hakea prostrata ) and sorghum ( Sorghum bicolor ) were confirmed to have single‐gene origin from the corresponding HpPEPC and SbPEPC genes (Shane et al ., ; Ruiz‐Ballesta et al ., ), suggesting that a similar relationship may exist for the p107 and p110 PEPC proteins in A. thaliana . The percentage of p110 was approximately 40% lower in the induced TPS29.2 plants than in the controls (Figure a).…”
Section: Resultsmentioning
confidence: 86%
“…PEPC-k activity seems to be regulated only at the level of synthesis/degradation, in response to light in C 4 Shenton et al 2006;Monreal et al 2010a) and C 3 (Gousset-Dupont et al 2005) plants, and by a circadian mechanism in CAM plants (Taybi et al 2000). Monoubiquitination (Uhrig et al 2008;Shane et al 2013;Ruiz-Ballesta et al 2014) or interaction with anionic phospholipids (Monreal et al 2010b) have recently been described as mechanisms introducing posttranslational modifications to PEPC. Interestingly, both modifications result in the inhibition of PEPC activity at least in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory PTPC monoubiquitination has been demonstrated in the endosperm of germinating castor oil seeds (COS) ( Uhrig et al , 2008 ), in developing proteoid roots of P-deficient harsh hakea ( Shane et al , 2013 ), and in lily pollen ( Igawa et al , 2010 ). A recent study by our group has shown monoubiquitination of SbPPC3 in sorghum, a cereal with starch-storing seeds ( Ruiz-Ballesta et al , 2014 ). Monoubiquitination is inhibitory as it results in increased K m (PEP) values and enhanced sensitivity to allosteric inhibitors ( Uhrig et al , 2008 ; Shane et al , 2013 ; Ruiz-Ballesta et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It catalyses the irreversible β-carboxylation of PEP to form oxaloacetate (OAA) and orthophosphate (P i ) (Chollet et al ., 2006). The plant-type PEPC ( PTPC ) genes encode closely related 100–110kDa polypeptides that typically exist as Class-1 PEPC tetramers that are post-translationally regulated by a combination of several allosteric effectors, including Glc-6-P (activation) and L-malate (inhibition), reversible phosphorylation ( Nimmo, 2003 ; O’Leary et al , 2011 a ), and monoubiquitination ( Uhrig et al , 2008 , Shane et al , 2013 ; Ruiz-Ballesta et al , 2014 ). The metabolite control is integrated with the enzyme’s reversible phosphorylation at a highly conserved serine residue located near the N-terminus of its PTPC subunits ( Chollet et al , 1996 ; Echevarría and Vidal, 2003 ; O’Leary et al , 2011 a ).…”
Section: Introductionmentioning
confidence: 99%